(Comparison Study of The Effectiveness of Cs, Na, Ca and Ba as Ionization Suppressant in The Determination of K Using AAS Technique) - Sait, Salya; Asnadi, Chepy (Warta Industri Hasil Pertanian, 1989)
Recommended method for the determination of potassium using the Air-Acetylene Flame AAS technique requires an addition of cesium cation which is expensive (dua to a scarcity of supply in Indonesia) to suppress ionization suppressant is investigaed and compared with that of cesium cation.The results of investigation conclude that only sodium cation is capable to substitute cesium cation in the method.